Seed Adaptive Traits of Fagus sylvatica Populations in Northeastern Greece. Issue 4 (21st February 2020) - Varsamis, Georgios; Merou, Theodora; Takos, Ioannis; Malesios, Chrisovalantis; Manolis, Apostolos; Papageorgiou, Aristotelis C
Abstract: Fagus sylvatica in Europe is expected to be severely affected by the ongoing climate change. In this article, seed adaptive traits, in terms of morphology and germination, of F. sylvatica populations of different postglacial lineage and intrapopulation genetic diversity were evaluated. Eight plots from two geographical provenances, Evros and Drama, were selected. Provenance shaped both morphology and germination patterns, but the effect was more pronounced on germination. Seeds from Drama were larger and heavier than those from Evros but exhibited a higher degree of dormancy and slower germination. High among-plots variability on morphology and germination was also observed, especially in Evros. This higher variability was consistent with the higher level of genetic diversity observed at genomic and chloroplast DNA markers at small or larger spatial scales from previous published studies on the same plots. Results suggested the existence of different seed adaptation strategies, mainly between provenances, as a result of possible adaptation to different environmental conditions, whereas a possible influence of a generally complex pattern of admixture between different beech subspecies and postglacial lineages could not be excluded.